The autoscopy process as a source of reflection for educational action in science classes - Codato, Marcos Vinícius Ferreira [UNESP]; Gomes, Paulo César [UNESP] (Investigacoes em Ensino de Ciencias (IENCI), 2022)
This article aims to investigate the process of self-reflection and the development of the autonomy of one biological science graduate teacher, who worked in different classes of Elementary School in the State of Paraná, based on the proposal of the Reflexive Teacher of Schön (1987) to study Dewey's work (1979a; 1979b; 1976) and contemporary works such as Carvalho e Passos (2014), Sadalla e Larocca (2004), Rosa-Silva (2008) and Pissolato e Lorencini Júnior (2021), among others. Through video recording at different stages of the data collection proposal considered here, that is, conducting semi-structured interviews, uninterrupted recording of classes before and after the intervention, interviews in front of the video and 'in loco' observation and; considering the three-phase autoscopy proposal proposed by Rosa-Silva (2008), we developed a personalized proposal that allowed the self-reflection and development of teaching autonomy provided by the self-analysis of science classes. With this study, it was possible to show that the proposal of triphasic autoscopy is an important tool for teacher education and that the participating teacher, by experiencing the reflexive process and its steps in a (more) conscious way, were able to restructure their classes and, as a subject of their own profession, better understand their own educational action in science.
O PROCESSO DE AUTOSCOPIA COMO FONTE DE REFLEXÃO PARA A AÇÃO EDUCATIVA EM AULAS DE CIÊNCIAS
Keywords: in-service teacher education; reflective teacher; self-reflection; triphasic autoscopy